Iron-based amorphous nanocrystalline alloy and preparation method thereof, amorphous iron core and application thereof
By using iron -based amorphous nanocrystalline alloys, using high -content CO, low content Si, and large -sized atoms to form a dual structure of amorphous nanocrystalline, solve the existing iron -based amorphous alloy high and saturated magnetic induction in high -frequency motor in high -frequency motors. The problem of insufficient strength realizes high -efficiency and low -noise high -frequency motor iron movements.
Patent Information
- Application Number
- CN202210513188.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-11
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-05-11
AI Technical Summary
The existing iron-based amorphous alloys have high iron loss and insufficient saturation magnetic induction strength in high-frequency motors, which limits their application in high-power and high energy density scenarios, and there are also major noise problems.
Using iron -based non -crystal nanocrystalline alloys, its chemical formula is FEACOBSICBDMECUF, through high content CO, low content Si and large -sized atoms such as V, TA, NB Lend the telescopic coefficient.
The high saturation magnetic induction strength (not less than 1.70T) and the low magnetic telescopic coefficient (less than 13ppm) of iron -based non -crystal nanocrystalline alloys (less than 13ppm) are reduced, and it is suitable for high -power and high -energy density scenarios.
Smart Images

Figure CN114974784B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of metal materials, and in particular to an iron-based amorphous nanocrystalline alloy and a preparation method thereof, an amorphous iron core and applications thereof. Background Art
[0002] The AC loss (i.e. iron loss) of the motor's soft magnetic core accounts for about 40% of the total motor loss. As the motor speed and frequency continue to increase, the proportion of iron loss will increase rapidly, so core loss becomes a key factor affecting the efficiency of high-frequency motors. At present, non-oriented silicon steel is one of the most widely used soft magnetic materials in motor cores. Its advantage is its high saturation magnetic induction intensity (1.8-2.1T), but its high coercive force and low resistivity result in large iron losses. As the frequency increases, the steel loss of silicon steel will increase exponentially, leading to overheating or even burning of the motor during the operation of high-frequency / high-speed motors.
[0003] Therefore, iron-based amorphous alloys are used to replace non-oriented silicon steel. Iron-based amorphous alloys are used in high-frequency motor stator cores (>500Hz). Compared with silicon steel materials, the iron loss of the core made of iron-based amorphous alloys can be reduced by 80-90%, and the power density of the motor can be increased by about 45%. The use of amorphous alloy materials to prepare motor cores will break through the technical bottleneck of low efficiency caused by excessive high-frequency loss of silicon steel cores in traditional motors, and is expected to bring about the upgrading of high-frequency and high-efficiency motors.
[0004] However, the saturation magnetic induction intensity (Bs) of the widely used iron-based amorphous alloy (grade 1K101) is 1.56T, which is much lower than that of traditional silicon steel (1.8-2.1T). This limits the application of iron-based amorphous alloys in high-power and high-energy density scenarios. Secondly, iron-based amorphous soft magnetic alloys have a large magnetostriction coefficient, which causes amorphous motors to generate large noise during use. Summary of the invention
[0005] In view of the deficiencies in the prior art, the purpose of the embodiments of the present application includes providing an iron-based amorphous nanocrystalline alloy and a preparation method thereof, an amorphous iron core and applications thereof, which can make the saturation magnetic induction intensity higher and the magnetostriction coefficient lower.
[0006] In a first aspect, the present invention provides an iron-based amorphous nanocrystalline alloy, the chemical formula of which is: Fe a Co b Si c B d M e Cu f; Wherein, M is one or a combination of V, Ta, Nb, a, b, c, d, e, f are the atomic percentages of the corresponding elements, 50≤a≤85, 8<b≤26, 0<c≤6, 6<d≤14, 0<e≤2, 0≤f≤1.5, a:b=(4~19):1, and a+b+c+d+e+f=100.
[0007] In the above technical solution, the Co content is relatively high, and the atomic percentage ratio of Fe to Co is a:b=(4-19):1. At the same time, the silicon content is relatively low, and large-sized atoms such as V, Ta, and Nb are added, which can hinder the movement of Fe, Co, Si, and B atoms during the material generation process and improve the alloy forming ability, thereby making the amorphous nanocrystalline dual-phase structure material have a higher saturation magnetic induction intensity and a lower magnetostriction coefficient.
[0008] In some embodiments of the present application, 68≤a≤70, 10≤b≤20, 0<c≤3, 10<d≤14, 80≤a+b≤85, a:b=(4~9):1, e:f=(0.5~1):1.
[0009] In the above technical solution, the atomic percentage corresponding to each element of the iron-based amorphous nanocrystalline alloy meets the above conditions, which can make the material have a higher saturation magnetic induction intensity, a lower magnetostriction coefficient, and a smaller coercive force.
[0010] In some embodiments of the present application, the chemical formula of the iron-based amorphous nanocrystalline alloy is: 0.8 Co 0.2 ) 85 SiC 12 V 0.5 Cu 0.5 or (Fe 0.8 Co 0.2 ) 85 Si 1.5 B 12 V 0.5 Cu1.
[0011] In some embodiments of the present application, the saturation magnetic induction intensity of the iron-based amorphous nanocrystalline alloy is not less than 1.80 T, the coercive force is not higher than 5 A / m, and the magnetostriction coefficient is less than 13 ppm.
[0012] In a second aspect, the present application provides an amorphous iron core, comprising the above-mentioned iron-based amorphous nanocrystalline alloy.
[0013] Using iron-based amorphous nanocrystalline alloys to prepare amorphous cores can reduce the iron loss of the cores and enable them to be used in high-power and high-energy density scenarios.
[0014] In a third aspect, the present application provides an application of an amorphous iron core in an amorphous motor or an amorphous transformer.
[0015] After the amorphous iron core is used in an amorphous motor or an amorphous transformer, the power density of the amorphous motor or the amorphous transformer can be improved, the efficiency is higher, and the noise is lower.
[0016] In a fourth aspect, the present application provides a method for preparing an iron-based amorphous nanocrystalline alloy, comprising:
[0017] According to the contents of various elements in the chemical formula of the iron-based amorphous nanocrystalline alloy, various raw materials are weighed in mass percentage and mixed to obtain a mixed raw material;
[0018] The mixed raw materials are melted to obtain alloy liquid, and the alloy liquid is sprayed onto the surface of a metal roller to obtain an iron-based amorphous alloy strip;
[0019] The iron-based amorphous alloy strip is subjected to transverse magnetic annealing to obtain the iron-based amorphous nanocrystalline alloy strip.
[0020] In the above technical solution, the iron-based amorphous nanocrystalline alloy prepared by this method has a higher saturation magnetic induction intensity and a lower magnetostriction coefficient.
[0021] In some embodiments of the present application, the metal roller is a copper roller, and the rotation speed of the copper roller is 30-40 m / s. The metal roller is a copper roller, which has better thermal conductivity and can cool the alloy melt more quickly; at the same time, limiting the rotation speed of the copper roller within the above range can make the strip formation more uniform and dense.
[0022] In some embodiments of the present application, the transverse magnetic annealing conditions are: heat treatment for 10 minutes or more under vacuum or nitrogen protection, magnetic field of 0.05-0.1T, temperature of 380-450°C. This can make the effect of transverse magnetic annealing better, so as to obtain an iron-based amorphous nanocrystalline alloy with better performance.
[0023] In some embodiments of the present application, the thickness of the strip is 20-21 μm, which is beneficial for preparing an amorphous iron core. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 A process flow chart of a method for preparing an iron-based amorphous nanocrystalline alloy provided in an embodiment of the present application;
[0026] Figure 2 The DSC curve of the iron-based amorphous nanocrystalline alloy provided in Example 1;
[0027] Figure 3 The BH curve of the iron-based amorphous nanocrystalline alloy provided in Example 1;
[0028] Figure 4 The effective magnetic permeability curve of the iron-based nanocrystalline alloy provided in Example 1;
[0029] Figure 5 This is a TEM photo of the iron-based amorphous nanocrystalline alloy provided in Example 1. DETAILED DESCRIPTION
[0030] Among the existing amorphous alloys, there are mainly 1K01 and 1K107 amorphous alloys. The chemical formula of 1K01 amorphous alloy is: Fe 78 Si 13 B9, its saturation magnetic induction intensity is only 1.56T; the chemical formula of the amorphous alloy with the grade 1K107 is: Fe 73.5 Cu1Nb3Si 13.5 B9, its saturation magnetic induction intensity is only 1.24T.
[0031] If the above two materials are used to prepare the core of an amorphous motor, although the iron loss of the core can be reduced, its saturation magnetic induction intensity is also low, which makes the amorphous motor unable to be used in high-power, high-energy density and other scenarios, and its use environment is limited.
[0032] Therefore, the present application provides an iron-based amorphous nanocrystalline alloy, which has a high saturation magnetic induction intensity. When the amorphous iron core is prepared by using the iron-based amorphous nanocrystalline alloy, the amorphous motor or amorphous transformer using the amorphous iron core can be used in high-power, high-energy-density and other scenarios, and the use environment is wider. At the same time, the magnetostriction coefficient of the iron-based amorphous nanocrystalline alloy is low. When the amorphous iron core is prepared by using the iron-based amorphous nanocrystalline alloy, the noise of the amorphous motor or amorphous transformer using the amorphous iron core can be reduced.
[0033] The chemical formula of the iron-based amorphous nanocrystalline alloy is: Fe a Co b Si c B d M e Cu f ; Wherein, M is one or a combination of V, Ta, Nb, a, b, c, d, e, f are the atomic percentages of the corresponding elements, 50≤a≤85, 8<b≤26, 0<c≤6, 6<d≤14, 0<e≤2, 0≤f≤1.5, a:b=(4~19):1, and a+b+c+d+e+f=100.
[0034] In the above-mentioned iron-based amorphous nanocrystalline alloy, since the Co content is relatively high and the atomic percentage ratio of Fe to Co is a:b=(4-19):1, at the same time, the silicon content is relatively low, and large-sized atoms such as V, Ta, and Nb are added, the movement of Fe, Co, Si, and B atoms can be hindered during the material generation process, and the alloy forming ability can be improved, thereby making the saturation magnetic induction intensity of the amorphous nanocrystalline dual-phase structure material higher and the magnetostriction coefficient lower.
[0035] Optionally, 68≤a≤70, 10≤b≤20, 0<c≤3, 10<d≤14, 80≤a+b≤86, a:b=(4~9):1, e:f=(0.5~1):1. The atomic percentages corresponding to the elements of the iron-based amorphous nanocrystalline alloy satisfy the above conditions, which can make the material have a higher saturation magnetic induction intensity, a lower magnetostriction coefficient, and a smaller coercive force.
[0036] For example: The chemical formula of iron-based amorphous nanocrystalline alloy is: (Fe 0.8 Co 0.2 ) 85 SiC 12 V 0.5 Cu 0.5 or (Fe 0.8 Co 0.2 ) 85 Si 1.5 B 12 V 0.5 In other embodiments, the chemical formula of the iron-based amorphous nanocrystalline alloy may also be: (Fe 0.9 Co 0.1 ) 86 SiC 11 V 0.5 Cu 0.5 .
[0037] In other embodiments, the chemical formula of the iron-based amorphous nanocrystalline alloy may also be: 0.8 Co 0.2 ) 85 SiC 12 Ta 0.5 Cu 0.5 , (Fe 0.8 Co 0.2 ) 85 Si 1.5 B 12 Ta 0.5 Cu1、(Fe 0.9 Co 0.1 ) 86 SiC 11 Ta 0.5 Cu0.5 , (Fe 0.8 Co 0.2 ) 85 SiC 12 Nb 0.5 Cu 0.5 , (Fe 0.8 Co 0.2 ) 85 Si 1.5 B 12 Nb 0.5 Cu1、(Fe 0.9 Co 0.1 ) 86 SiC 11 Nb 0.5 Cu 0.5 .
[0038] In other embodiments, the chemical formula of the iron-based amorphous nanocrystalline alloy may also be: 0.9 Co 0.1 ) 85 SiC 12 V 0.5 Cu 0.5 , (Fe 0.8 Co 0.2 ) 86 SiC 11 V 0.5 Cu 0.5 .
[0039] The iron-based amorphous nanocrystalline alloy provided in the present application has a saturation magnetic induction intensity of not less than 1.70 T, a coercive force of not more than 6 A / m, and a magnetostriction coefficient of less than 13 ppm.
[0040] Optionally, the saturation magnetic induction intensity of the iron-based amorphous nanocrystalline alloy is 1.80-1.95 T, the coercive force is 4-4.8 A / m, and the magnetostriction coefficient is less than 12 ppm.
[0041] Exemplarily, the saturation magnetic induction intensity of the iron-based amorphous nanocrystalline alloy is 1.70T, 1.72T, 1.74T, 1.76T, 1.78T, 1.80T, 1.82T, 1.84T, 1.86T, 1.88T, 1.90T, 1.92T or 1.95T; the coercive force of the iron-based amorphous nanocrystalline alloy is 4A / m, 4.2A / m, 4.4A / m, 4.6A / m, 4.8A / m, 5A / m, 5.2A / m, 5.4A / m, 5.6A / m, 5.8A / m or 6A / m; the magnetostriction coefficient of the iron-based amorphous nanocrystalline alloy is 9ppm, 10ppm, 11ppm, 12ppm or 13ppm.
[0042] The above-mentioned iron-based amorphous nanocrystalline alloy can be used to prepare an amorphous iron core and applied to an amorphous motor or an amorphous transformer. The use of an iron-based amorphous nanocrystalline alloy to prepare an amorphous iron core can reduce the iron loss of the iron core and can be applied in high-power and high-energy density scenarios; and the noise is also low.
[0043] After introducing the iron-based amorphous nanocrystalline alloy material above, its preparation method is specifically introduced below. Figure 1 For a process flow chart of the preparation method of the iron-based amorphous nanocrystalline alloy provided in the embodiment of the present application, please refer to Figure 1 , the preparation method comprises the following steps:
[0044] S110, according to the content of various elements in the chemical formula of the iron-based amorphous nanocrystalline alloy, various raw materials are weighed in mass percentage and mixed to obtain a mixed raw material; the chemical formula of the iron-based amorphous nanocrystalline alloy is: Fe a Co b Si c B d M e Cu f ; Wherein, M is one or a combination of V, Ta, Nb, a, b, c, d, e, f are the atomic percentages of the corresponding elements, 50≤a≤85, 8<b≤26, 0<c≤6, 6<d≤14, 0<e≤2, 0≤f≤1.5, a:b=(4~19):1, and a+b+c+d+e+f=100.
[0045] S120, melting the mixed raw materials to obtain alloy liquid, and spraying the alloy liquid onto the surface of the metal roller to obtain an iron-based amorphous alloy strip.
[0046] Optionally, the smelting method is: smelting the mixed raw material provided in step S110 to obtain alloy liquid and cooling it to obtain a master alloy ingot. The smelting can be performed multiple times, and slag can be removed during each smelting to obtain a master alloy ingot with higher purity.
[0047] Optionally, the master alloy ingot is melted to obtain alloy liquid and sprayed onto the surface of the metal roller to obtain the iron-based amorphous alloy strip. The rotation speed of the metal roller can be 30 to 40 m / s. Limiting the rotation speed of the copper roller within the above range can make the formation of the strip more uniform and dense. For example, the rotation speed of the metal roller can be 30 m / s, 32 m / s, 34 m / s, 36 m / s, 38 m / s or 40 m / s.
[0048] Optionally, the metal roller is a copper roller, which has better thermal conductivity and can cool the alloy melt more quickly. The copper roller can be made entirely of copper material, or can be a roller structure with a copper layer on the surface.
[0049] S130, performing transverse magnetic annealing on the iron-based amorphous alloy strip to obtain the iron-based amorphous nanocrystalline alloy strip. The iron-based amorphous nanocrystalline alloy prepared by the method has a high saturation magnetic induction intensity and a low magnetostriction coefficient.
[0050] Optionally, the transverse magnetic annealing condition is: heat treatment for 10 minutes or more under vacuum or nitrogen protection, magnetic field of 0.05-0.1T, temperature of 380-450°C. This can make the transverse magnetic annealing effect better, so as to obtain an iron-based amorphous nanocrystalline alloy with better performance.
[0051] Optionally, the magnetic field of transverse magnetic annealing can be 0.05T, 0.06T, 0.07T, 0.08T, 0.09T or 0.1T; the temperature of transverse magnetic annealing can be 380℃, 390℃, 400℃, 410℃, 420℃, 430℃, 440℃ or 450℃; the time of transverse magnetic annealing can be 10min, 15min, 20min, 25min, 30min, 35min, 40min, 45min, 50min, 55min or 60min.
[0052] The chemical formula of the iron-based amorphous nanocrystalline alloy prepared by the above method is Fe a Co b Si c B d M e Cu f ; Wherein, M is one or a combination of V, Ta, and Nb, a, b, c, d, e, and f are the atomic percentages of the corresponding elements, 50≤a≤85, 8<b≤26, 0<c≤6, 6<d≤14, 0<e≤2, 0≤f≤1.5, a:b=(4~19):1, and a+b+c+d+e+f=100; the saturation magnetic induction intensity is not less than 1.70T, the coercive force is not higher than 6A / m, and the magnetostriction coefficient is less than 13ppm; it is in the shape of a strip, and the thickness of the strip is 20~21μm.
[0053] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0054] Example
[0055] The preparation method of amorphous nanocrystalline alloy comprises the following steps:
[0056] (1) Weigh and prepare the ingredients according to the chemical formula of the amorphous nanocrystalline alloy, and repeatedly melt the ingredients three times to make the master alloy components melt evenly; wherein the chemical formula of the amorphous nanocrystalline alloy is shown in Table 1.
[0057] (2) The smelted master alloy is induction heated to a molten state to obtain alloy liquid, which is quickly sprayed onto the surface of a rapidly rotating copper roller to obtain an iron-based amorphous alloy strip with a width of 1 mm and a thickness of 21 μm. The rotation speed of the copper roller is 30 to 40 m / s.
[0058] (3) Performing transverse magnetic annealing on the iron-based amorphous alloy strip to obtain an iron-based amorphous nanocrystalline alloy strip. The transverse magnetic heat treatment conditions are: heat treatment for 10 minutes under nitrogen protection, a magnetic field of 0.08T, and a temperature of 400°C.
[0059] The saturation magnetic induction intensity B of the obtained amorphous nanocrystalline alloy strips s Measurement, coercivity H c The magnetostriction coefficient was measured and the test results are shown in Table 1.
[0060] Among them, B s The 7410 vibrating sample magnetometer produced by Lake Shore Company in the United States was used for measurement. 2 to 3 strips of about 4 mm in length were selected as samples and weighed repeatedly 3 times with a high-precision electronic balance (accuracy: 0.01 mg). The sample was attached to the bottom of the round sample stage with double-sided tape and kept parallel to the test magnetic field along the length direction. The maximum magnetic field applied was 800 kA / m. The cast B s The value and annealing B s The value of cast B s The detection object is the iron-based amorphous alloy strip obtained in step (2); annealing B s The detection object is the iron-based amorphous nanocrystalline alloy strip obtained in step (3).
[0061] H c The measurement was performed using the EXPH-100 DC BH Curve Tracer produced by RIKEN, Japan. Two to three 8 cm long iron-based amorphous nanocrystalline ribbons obtained in step (3) were selected as samples and weighed three times using a high-precision electronic balance (accuracy: 0.01 mg). They were then attached to the center of the spiral tube with double-sided tape and the maximum magnetic field was 800 kA / m to obtain the annealed H c The value of .
[0062] Magnetostriction coefficient The iron-based amorphous nanocrystalline strip obtained in step (3) of cutting 10 mm in length was used to make two points at a distance of 40 μm for positioning using a nanoindenter (Hystrion Ti980). An AFM instrument (Oxford Instruments Asylum Research / Cypher S) was used to observe the distance between the indentation points in situ under 0 field and saturation magnetization field, respectively, to calculate the displacement change rate. It is known that the magnetostriction coefficient of 1K101 is about 30 ppm, and the magnetostriction coefficient of 1K107 is about 1 ppm. The magnetostriction coefficients of the alloys provided in the embodiment and the comparative example are obtained based on the displacement change rates of the three alloys.
[0063] Table 1 Chemical formula and properties of amorphous nanocrystalline alloys
[0064]
[0065]
[0066] It can be seen from Table 1 that the cast B of the iron-based amorphous nanocrystalline alloy provided in the embodiment of the present application s , after annealing B s The values are all large, reaching 1.70T and above; the magnetostriction coefficients are all small (≤13ppm). When ferromagnetic materials are magnetized, the length will be extended or shortened along the magnetization direction. A large magnetostriction coefficient indicates that the size of the ferromagnetic material changes dramatically, and the noise or vibration generated is large. In the embodiments of the present application, the magnetostriction coefficient of the iron-based amorphous nanocrystalline alloy is small, and when it is made into the core of an amorphous motor or an amorphous transformer for use, the noise can be greatly reduced.
[0067] Among them, the iron-based amorphous nanocrystalline alloy provided in Examples 1 and 2 not only has the cast B s , after annealing B s The values of are all large, reaching 1.80T and above; and after annealing, H c The values are all very small, no higher than 4.6A / m, and the magnetostriction coefficient is 11ppm, which makes the comprehensive performance of the iron-based amorphous nanocrystalline alloy better.
[0068] Figure 2 The DSC curve of the iron-based amorphous nanocrystalline alloy provided in Example 1; Figure 2 It can be seen that the first crystallization temperature Tx1 is 380° C., and the second crystallization temperature Tx2 is 530° C., indicating that this component has a relatively wide thermal treatment process window (ΔTx=150° C.).
[0069] Figure 3 The BH curve of the iron-based amorphous nanocrystalline alloy provided in Example 1; Figure 3It can be seen that the iron-based amorphous nanocrystalline alloy provided in Example 1 has a Bs of 1.92 T after annealing, and has a very high saturation magnetic induction intensity.
[0070] Figure 4 The effective magnetic permeability curve of the iron-based nanocrystalline alloy provided in Example 1; Figure 4 It can be seen that the effective magnetic permeability of the iron-based amorphous nanocrystalline alloy provided in Example 1 exceeds 8000 at 1 kHz.
[0071] Figure 5 TEM photo of the iron-based amorphous nanocrystalline alloy provided in Example 1; Figure 5 It can be seen that after annealing, sparse and discrete nanocrystals are precipitated in the iron-based amorphous nanocrystalline alloy provided in Example 1, and two nanocrystals of different phases are superimposed together, which is different from the distribution mode of traditional nanocrystals. Traditional nanocrystals precipitate a lot and there is no superposition between nanocrystals. The inventor speculates that this special nanocrystal precipitation mode is a transition state between amorphous alloys and traditional amorphous nanocrystalline alloys, which can make the iron-based amorphous nanocrystalline alloy provided in Example 1 reach Bs of 1.92T after annealing, and H c As low as 4.2A / m, magnetostriction coefficient as low as 11ppm.
[0072] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
Claims
1. An iron-based amorphous nanocrystalline alloy, characterized in that: The chemical formula of the iron-based amorphous nanocrystalline alloy is: 0.8 Co 0.2 ) 85 SiC 12 V 0.5 Cu 0.5 The iron-based amorphous nanocrystalline alloy precipitates nanocrystals after annealing, and two nanocrystals in different phases are superimposed together.
2. The iron-based amorphous nanocrystalline alloy according to claim 1, characterized in that: The iron-based amorphous nanocrystalline alloy has a saturation magnetic induction intensity of not less than 1.70 T, a coercive force of not more than 6 A / m, and a magnetostriction coefficient of less than 13 ppm.
3. An amorphous core, characterized in that: It comprises the iron-based amorphous nanocrystalline alloy as described in claim 1.
4. Use of the amorphous iron core according to claim 3 in an amorphous motor or an amorphous transformer.
5. A method for preparing the iron-based amorphous nanocrystalline alloy according to claim 1, characterized in that: include: According to the contents of various elements in the chemical formula of the iron-based amorphous nanocrystalline alloy, various raw materials are weighed in mass percentage and mixed to obtain a mixed raw material; The mixed raw materials are melted to obtain alloy liquid, and the alloy liquid is sprayed onto the surface of a metal roller to obtain an iron-based amorphous alloy strip; The iron-based amorphous alloy strip is subjected to transverse magnetic annealing to obtain an iron-based amorphous nanocrystalline alloy strip.
6. The preparation method according to claim 5, characterized in that: The metal roller is a copper roller, and the rotation speed of the copper roller is 30-40 m / s.
7. The preparation method according to claim 5, characterized in that: The transverse magnetic annealing conditions are: heat treatment for 10 minutes or more under vacuum or nitrogen protection, a magnetic field of 0.05-0.1T, and a temperature of 380-450°C.
8. The preparation method according to claim 5, characterized in that: The thickness of the strip is 20~21μm.
Citation Information
Patent Citations
Magnetic alloy, amorphous alloy ribbon, and magnetic part
CN101627140A
Low-frequency transformer
CN1037231A